Thorax and pelvis kinematics during the downswing of male and female skilled golfers - Horan, S. A.; Evans, K.; Morris, N. R.; Kavanagh, J. J. (Journal of Biomechanics, 2010)
Thorax and pelvis motion during the golf swing have most frequently been described for male golfers at discrete points during the swing, such as top of backswing (TBS) and ball contact (BC). Less is known about the continual motion and coordination of the thorax and pelvis throughout the downswing for either male or female golfers. The purpose of this study was to present detailed 3D kinematic profiles of thorax and pelvis motion during the downswing, and to determine if differences in kinematics exist between male and female skilled golfers. Thorax and pelvis data were collected from 19 male (26±7 years) and 19 female (25±7 years) skilled golfers (handicap =4) using an optical motion analysis system. 3D segment position, orientation and angular velocity were calculated, along with phase plane trajectories and thorax-pelvis separation angles. At BC males had greater pelvis posterior tilt, greater pelvis and thorax lateral tilt to the right, and less pelvis and thorax axial rotation to the left compared to females. Males achieved greater peak thorax and pelvis angular velocity, and angular velocity at BC, in the anterior-posterior and lateral tilt directions. Phase plane trajectories revealed that males and females had similar thorax lateral tilt and anterior-posterior tilt angular velocity-displacement relationships at TBS, yet by BC males had greater tilt angles and velocities compared to females. Collectively, the results suggest that male and female skilled golfers have different kinematics for thorax and pelvis motion, predominantly for lateral and anterior-posterior tilt. What might be considered optimal swing characteristics for male golfers should not be generalized to female golfers.